Congenital heart anomaly in newborns with congenital diaphragmatic hernia: a single‐center experience. (4th May 2015) - Ruano, R.; Javadian, P.; Kailin, J. A.; Maskatia, S. A.; Shamshirsaz, A. A.; Cass, D. L.; Zamora, I. J.; Sangi‐Haghpeykar, H.; Lee, T. C.; Ayres, N. A.; Mehollin‐Ray, A.; Cassady, C. I.; et al.
ABSTRACT Objective To evaluate the impact of the presence of a congenital heart anomaly (CHA) and its potential contribution to morbidity and mortality in infants with congenital diaphragmatic hernia (CDH). Methods In this retrospective cohort study, prenatal and postnatal data of all newborns diagnosed with CDH between January 2004 and December 2012 in a single center were reviewed. Cases were classified into two groups: those with 'isolated' CDH and those with both CDH and CHA. Patients with CHA were further subclassified into those with a major or minor CHA based on the Risk Adjustment for Congenital Heart Surgery‐1 (RACHS‐1), and the Society of Thoracic Surgeons–European Association for Cardiothoracic Surgery (STS‐EACTS) scoring systems. Patients with associated non‐cardiac anomalies, including 'syndromic cases', were excluded from the analysis. Primary and secondary outcomes were survival up to 1 year of age and a need for extracorporeal membrane oxygenation (ECMO), respectively. Results Of the 180 infants with CDH, 41 were excluded because of the presence of non‐cardiac associated anomalies, 118 had isolated CDH and 21 had CDH with CHA (16 with minor and five with major CHA). Receiver–operating characteristics curve analysis demonstrated that the best cut‐off for survival was when the score for CHA was ≤ 2 for both RACHS‐1 (area under the curve (AUC), 0.74 (P = 0.04); sensitivity, 80.0%; specificity, 87.5%) and STS‐EACTS (AUC, 0.83 (P = 0.03); sensitivity, 100%; specificity, 87.5%). Survival rate at 1 year was significantly lower in those with CHD and a major CHA (40.0%; P = 0.04) than in those with isolated CDH (77.1%) and those with CDH and a minor CHA (81.3%). We found no significant differences among the groups with regard to the need for ECMO. Conclusions In general, a milder form of CHA does not appear to have a negative impact on the survival of infants with CDH. However, mortality appears to be significantly higher in infants with CDH and a major form of CHA. The scoring systems appear to be useful as predictors for classifying the effects of CHA in this population of patients. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.